Design, synthesis, molecular dynamics studies and biological evaluations of 4-hydroxy-5-pyrrolinone-3-carbohydrazides as HIV-1 integrase inhibitors - Nafiseh Karimi; Amirreza Dowlati Beirami; Rouhollah Vahabpour Roudsari; Zahra Hajimahdi; Afshin Zarghi (European Journal of Medicinal Chemistry Reports)
Acquired immune deficiency syndrome (AIDS) diseases despite the efficacy of anti-HIV therapy, remain one of the human's most serious problems. Hence, the introduction of novel anti-HIV agents as first-line therapy is still required. HIV integrase lacking human enzyme homologous is an interesting target for developing new anti-HIV drugs. Following our attempts to describe active integrase inhibitor structures, here a series of novel 4-Hydroxy-5-pyrrolinone-3-carbohydrazides as HIV integrase inhibitor agents were identified. Biological results showed that all compounds could inhibit integrase strand transfer reaction and also exhibited anti-HIV activity in a cell-based assay. The interaction between integrase and designed compounds was investigated using molecular docking and molecular dynamics simulations.